Expert Method of Implementation of Funds ICT in the tax system - Achilov Salokhiddin Salomovich (International Journal on Orange Technologies, 2022)
Quality management and reliability of the introduction of modern information and communication technology (ICT) in the field of the state tax system is one of the cornerstones of the effective development of any investment in the real sectors of the country's economic life. Solving the problem of the quality of information technology implementation requires an integrated approach to managing objects of tax structures, as well as the maximum implementation of the principles and rules of services from supervisory authorities and business entities. The article discusses one of the new and non-standard approaches to solving the actual problem of assessing the quality of ICT implementation in the tax system associated with expert assessment, which will lead to the creation of convenience and transparency about the reports and calculations provided by taxpayers, by providing a wide range of modern and comfortable interactive state services. Therefore, the new approach considered in this article is relevant and important in connection with the need to improve the system for managing tax revenues to the budget and other obligatory payments, as well as to create a market economic mechanism for assessing the quality of interactive services provided by the state tax authorities of the Republic of Uzbekistan.